Implementation of Occupational Safety for Waste Processing Officers for Hazardous and Toxic Materials (B3) - Irmayani Irmayani; Rosita Ginting; Jul Asdar Samura; Anggi Isnani Parinduri; Sri Melda Bangun; Dewi F Handayani (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
The implementation of occupational safety principles plays a very important role for officers who handle B3 medical waste, considering that they interact directly with hazardous and toxic materials. This effort aims to create a safe, healthy, and pollution-free work environment, so as to minimize the occurrence of work accidents and health problems due to exposure in the workplace. This study uses a qualitative approach with the aim of exploring in depth the implementation of occupational safety in B3 medical waste processing officers at the Pagar Merbau Health Ceter, Deli Serdang Regency. There were three informants in this study, and data were obtained through observation and in-depth interviews. The results of the study showed that the implementation of occupational safety in the field has not been running optimally. One of the main obstacles is the lack of consistency of officers in using Personal Protective Equipment (PPE). Based on these results, it is recommended that K3 officers be more intensive in providing direction and supervision of the use of PPE and the implementation of work procedures according to applicable standards. This is important to ensure the safety and comfort of work for officers involved in the management of B3 medical waste.